A Persian Perspective on Grammaticalization of Future Marking - Mostafa Rahimi Rad (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Temporal references have been the subject of many studies around the world. Futurity is specially an elusive concept really difficult to perceive and describe. The present study tries to launch an investigation regarding the variability of future tense in Farsi. 130 sentences extracted from 8 interviews have been explored along with age, gender, presence or absence of temporal adverbial and animacy of the subject. 5 possible variabilities for expressing futurity are considered in the present study. Future time is especially difficult to perceive and in fact it might not occur. This forces us when it comes to the modality in which statements about the future may be interpreted. Not only do we just talk about those future events which are planned, but also that is the only (natural) modality that we can ascribe to those events. Following Fleischman (1982) and Comrie (1985), we suggest that the notion of future tense or futurity marking is a second class function, and the means available to futurity marking are typically borrowed from other constructions in the language However, before a further discussion of the circumstances giving rise to the idea, as well as some facts that seem to follow from this constraint on modality, we would like to give a brief sketch of some ways that futurity is expressed in different languages.